Integrating Local Linguistic Features into Rule-Based Chatbots: A Framework for Makassar Language Dialogue Systems - Thabrani. R Thabrani. R; Faizal Faizal; Suryani Suryani (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
The advancement of digital technology has transformed the way people communicate and access information; however, it has also led to a decline in the use of regional languages, including the Makassar language. This phenomenon highlights the need for language preservation efforts through technology-based approaches. This research was conducted at the Public Relations Bureau of the Makassar City Government with the aim of designing a web-based dialogue application using the Makassar language as an interactive medium to promote local culture and tourism. The study employed a qualitative approach through observation and literature review methods, and implemented the System Development Life Cycle (SDLC) model with the waterfall approach. The application was developed using PHP and JavaScript programming languages and adopted a rule-based method to build a chatbot capable of interacting naturally in the Makassar language. System testing was carried out using the black-box method to ensure functionality and reliability in responding to user inquiries. The results showed that the chatbot performed effectively, providing relevant information about Makassar City’s culture and tourism, and increasing public appreciation for local language and culture. This study concludes that the integration of web-based technology with regional languages not only contributes to cultural preservation but also strengthens communication between the government and the community in the context of digital transformation.